Estudo da relação do infiltrado inflamatório mononuclear e expressão de Ki-67, colágeno IV e laminina em cistos radiculares - Mourão, Renata Veras Carvalho (2013)
Jawbone cysts are classified as odontogenic and non-odontogenic cysts. The radicular cyst is the most common odontogenic cyst of inflammatory origin, whereas the detigerous cyst is the most common type of developmental odontogenic cyst. These cysts and their variations have different etiopathogenesis and biological behavior, but are equally lytic. The proliferation activity of the epithelial lining and the components of the basement membrane and extracellular matrix constitute targets of research. The aim of this study was to evaluate the relation between mononuclear inflammatory infiltrate and the expression of proliferative immunomarkers (Ki 67), and proteins of basement membrane and extracellular matrix in radicular cysts. In this retrospective observational study, all cases of jawbone cysts that had been recorded in the files of the Department of Pathology and Legal Medicine (FAMED), and of the Laboratory of Oral Pathology (FFOE) of the Federal University of Ceará (UFC) and reviewed. After histological revision, the groups were divided into heavily inflamed radicular cysts (HIRC) (n=17), slightly inflamed radicular cysts (SIRC) (n=9) and dentigerous cysts (DC) (n=9). The presence and intensity of the lymphoplasmacytic inflammatory infiltrate and the preservation of the epithelial lining were the parameters used to select the cases. Immunohistochemical analyses were performed using the standard streptavidin-biotin-peroxidase method. The primary antibodies used in this study included Ki 67 (Dako®, 1:50), Anti-Collagen Type IV (DBS®, 1:40) and Anti- Laminin (DBS®, 1:20).The immunoexpression of Ki-67 was more intense in the SIRC group compared to the HIRC group and DC. Likewise, the immunoexpression of Anti-Collagem Type IV in the basement membrane of the SIRC group presented a statistically significant difference compared to the HIRC group and DC . The expression of laminin in the basement membrane and in group HIRC and DC was negative and the group of SIRC was weak and punctual. It was concluded that presence and severity of inflammatory content wall of radicular cysts appear to modify the expression of proliferation factors in the coating epithelium and collagen type IV and laminin in the basement membrane but not modific with the behavior of extracellular matrix in radicular cyst. The expression of basement membrane components (laminin and collage type IV) is higher in radicular cyst with mild inflammatory infiltrade.